ChemInform Abstract: Facile Access to 1H‐Indazoles Through Iodobenzene‐Catalyzed C—H Amination under Mild, Transition‐Metal‐Free Conditions. Issue 8 (February 2015) - Kashiwa, Mitsuhiro; Sonoda, Motohiro; Tanimori, Shinji
Abstract Multisubstituted 1H‐indazoles having an N‐aryl substituent are prepared by iodobenzene‐catalyzed oxidative intramolecular C‐H amination of hydrazones.